Transformation of University Vision and Mission Under New Leadership: Strategic Steps Towards a Global University - Abdul Jalil; Ramadhan Tosepu (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: The selection of a competent and integrity-driven Chancellor for Halu Oleo University (UHO) for the 2025–2029 term is a shared aspiration that plays a crucial role in advancing the institution’s academic reputation and organizational performance. As such, the rectoral election serves as a strategic opportunity to shape UHO’s leadership direction and institutional transformation in response to national and global challenges. Objective: This study seeks to support the UHO rectoral election by proposing a future-oriented vision and mission aligned with the university’s strategic priorities. It also aims to assess how well the candidates’ proposed vision and mission statements reflect UHO’s institutional needs, values, and long-term development goals. Methods: Employing a qualitative approach, the research involves a comprehensive review of the election process, institutional challenges, and strategic priorities. Data collection includes document analysis of the candidates’ vision and mission statements, and examination of the university’s electoral structure, which comprises 49 Senate members 22 ex officio and 27 elected faculty representatives. Results: All Senate members participated as voters. The candidates’ proposals primarily focus on enhancing academic quality, research innovation, and community engagement. Conclusion: A transparent and integrity-based election process is vital for promoting progressive, accountable, and globally competitive leadership at UHO. Keywords: rectoral election, academic leadership, Halu Oleo University, strategic governance, university vision and mission